Augmented Reality as A Display Information Using Quick Sort - Astrid Novita Putri; Siti Asmiatun (IJAIT (International Journal of Applied Information Technology), 2018)
Information media of technology nowadays becomes a very easy means to convey information, and one of the recent technologies that still develop is augmented reality, which is used as information media. Augmented reality can integrate an image target and can be implemented easily. This technology utilizes an object tracing and uses detail feature from every camera object, after that it can be applied to all smartphones. By taking advantage of this technology, the augmented reality, and using logo marker and animation video, Faculty of Information and Communication Technology Semarang University can share information of its activities and can attract many people's attention to know further about activities held by this faculty. This research focuses on the augmented reality which will show the activities ranking, the activities held by the Faculty of Information and Communication Technology. The activities are shown by animation video using quick sort method to display them based on the most number of activities held by each study program. The result of this research finds out that study program of communication technology holding the first ranking. This study program holds the most often activities so the number of activities is the highest. The application can be displayed virtually using a smartphone and developed using Unity 3D and Vuforia.